1983
DOI: 10.1111/j.1469-8137.1983.tb04865.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Periods of Localized Water Stress on Subsequent Nutrient Uptake by Barley Roots and Their Adaptation by Osmotic Adjustment

Abstract: SUMMARYDrought and low soil water potentials depress nutrient uptake by roots, but their capacity for recovery when the soil is re-wetted has received less study. We investigated the uptake in barley of labelled phosphate and calcium from sand culture following periods of drought or treatment with polyethylene glycol 4000 (PEG) of the surface layers of the sand, with the lower portion of the root system receving ample nutrients and water. Drought diminished uptake and translocation of both nutrients and caused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

1987
1987
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 35 publications
(28 reference statements)
1
7
1
Order By: Relevance
“…This estimated value is similar to that calculated from the nutrient culture experiments despite the assumption that all roots were exposed to a uniform average herbicide concentration in the soil. Shone & Flood (1983) also found no compensatory increase in root weight in non-stressed compared to drought-stressed parts of root systems which contrasts with other reports of compensatory uptake of water (e.g. Where only the primary or secondary roots were treated with 1 pg/l5 ml/l 1 days (Table 2) there was no evidence of increased nutrient solution uptake by the untreated roots.…”
Section: Estimated Entry Of Isoproturon Into Plants Growing In Soilcontrasting
confidence: 93%
“…This estimated value is similar to that calculated from the nutrient culture experiments despite the assumption that all roots were exposed to a uniform average herbicide concentration in the soil. Shone & Flood (1983) also found no compensatory increase in root weight in non-stressed compared to drought-stressed parts of root systems which contrasts with other reports of compensatory uptake of water (e.g. Where only the primary or secondary roots were treated with 1 pg/l5 ml/l 1 days (Table 2) there was no evidence of increased nutrient solution uptake by the untreated roots.…”
Section: Estimated Entry Of Isoproturon Into Plants Growing In Soilcontrasting
confidence: 93%
“…For example, Larrea tridentata exhibited a fivefold increase in d 15 N as soon as 3 days after watering, compared to unwatered controls (BassiriRad et al 1999). Nutrient uptake recovery in Larrea was attributed primarily to increased root growth, similar to that found in wheat (Brady et al 1995) and barley (Shone and Flood 1983).…”
Section: Effects Of Water and Temperaturementioning
confidence: 66%
“…Although we suggest that post-drought recovery of NOS uptake was uncoupled from root growth in A. tridentata seedlings, the potential contribution of root growth to recovery of water and other nutrient uptake should not be underestimated (Shone and Flood 1983;Lauenroth et al 1987;North and Nobel 1991;Thomas 1991). Recovery of q,, reported within 4 days after rewetting (Fig.…”
Section: Discussionmentioning
confidence: 80%
“…after a rainfall event, results in increased water uptake and resumption of plant water status (Nobel and Sanderson 1984;Lauenroth et al 1987). Rapid root proliferation following rewetting may also be a plastic response adapted to resume nutrient uptake, particularly for slow diffusing ions such as P (Shone and Flood 1983). However, more recently Jupp and Newman (1987) reported that post-drought P uptake in pre-stressed rye grass was unrelated to initiation of root growth.…”
Section: Discussionmentioning
confidence: 99%